Targeted Glucose or Glutamine Metabolic Therapy Combined With PD-1/PD-L1 Checkpoint Blockade Immunotherapy for the Treatment of Tumors - Mechanisms and Strategies - Ma, Guofeng; Li, Chun; Zhang, Zhilei; Liang, Ye; Liang, Zhijuan; Chen, Yuanbin; Wang, Liping; Li, Dan; Zeng, Manqin; Shan, Wenhong; Niu, Haitao (Frontiers in Oncology, 2021)
Immunotherapy, especially PD-1/PD-L1 checkpoint blockade immunotherapy, has led tumour therapy into a new era. However, the vast majority of patients do not benefit from immunotherapy. The reason for this lack of response may be that the association between tumours, immune cells and metabolic reprogramming in the tumour microenvironment affect tumour immune escape. Generally, the limited amount of metabolites in the tumour microenvironment lead to nutritional competition between tumours and immune cells. Metabolism regulates tumour cell expression of PD-L1, and the PD-1/PD-L1 immune checkpoint regulates the metabolism of tumour and T cells, which suggests that targeted tumour metabolism may have a synergistic therapeutic effect together with immunotherapy. However, the targeting of different metabolic pathways in different tumours may have different effects on tumour immune escape. Herein, we discuss the influence of glucose metabolism and glutamine metabolism on tumour immune escape and describe the theoretical basis for strategies targeting glucose or glutamine metabolism in combination with PD-1/PD-L1 checkpoint blockade immunotherapy.